A multilayer composite electrode structure for a piezoresistor

CN224907685UActive Publication Date: 2026-10-27ZHEJIANG WRDZ ELECTRONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202521399312.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2026-10-27
Estimated Expiration
2035-07-04

AI Technical Summary

Technical Problem

[0002]现有技术中电涌保护器用的MOV一般是用银作为导电和焊接电极,银电极导电性能好但也有很多缺陷,如银质软熔点低,附着力比较低,在多次雷击或多脉冲大通流的冲击中由于附着力低、电迁移现象等问题下会因为银质电极的材质与工艺缺陷导致外部焊接的电极脱落或接触不良造成产品性能低下,使该有的防卫功能不能得到实际性的作用

Benefits of technology

[0016]本实用新型的有益效果:本实用新型中采用铬或氮化钛或钛层等材料作为第一功能功能层,使电极与MOV基片的剥离强度大大提升有效解决电极分层问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224907685U_ABST
    Figure CN224907685U_ABST
Patent Text Reader

Abstract

The utility model discloses a multilayer composite electrode structure's piezoresistor, its characterized in that, including MOV substrate, the first functional layer of direct adhesion in MOV substrate surface, the first functional layer is the layer of one or more materials selected from titanium, nickel chromium alloy, chromium, molybdenum, tantalum, titanium nitride or nickel, adhesion on the second functional layer of the first functional layer, the second functional layer is copper layer, wherein, the distance of the four edges of the composite electrode that the first functional layer and second functional layer constitute and the four edges of MOV substrate is 0.1 3mm. In the utility model, adopt chromium or titanium nitride or titanium layer and so on material as the first functional functional layer, make the peeling strength of electrode and MOV substrate greatly promote effectively solve the electrode delamination problem.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This utility model relates to the field of surge protector technology, specifically to a multi-layer composite electrode structure varistor, which is particularly suitable for high surge current and multi-pulse impact scenarios. Background Technology

[0002] In existing surge protectors, the MOVs used generally use silver as the conductive and welding electrode. While silver electrodes have good conductivity, they also have many drawbacks, such as a low melting point and low adhesion. Under repeated lightning strikes or impacts from multiple pulses and high currents, the low adhesion and electromigration can cause the externally welded electrodes to detach or make poor contact due to defects in the material and manufacturing process of the silver electrodes, resulting in poor product performance and rendering the intended protective function ineffective. Summary of the Invention

[0003] The purpose of this invention is to provide a varistor with a multilayer composite electrode structure, which improves the adhesion between the electrodes and the MOV substrate, preventing detachment. It also enhances the high-temperature resistance of the electrodes, resisting high-current surges. Furthermore, it optimizes current distribution, suppresses electromigration, and increases current-carrying capacity.

[0004] To achieve the above objectives, this utility model provides the following technical solution:

[0005] A varistor with a multilayer composite electrode structure, characterized in that it comprises: an MOV substrate; a first functional layer directly attached to the surface of the MOV substrate, the first functional layer being a layer composed of one or more materials selected from titanium, nickel-chromium alloy, chromium, molybdenum, tantalum, titanium nitride, or nickel; and a second functional layer attached to the first functional layer, the second functional layer being a copper layer; wherein the distance between the four edges of the composite electrode formed by the first functional layer and the second functional layer and the four edges of the MOV substrate is 0.1-3 mm.

[0006] The present invention further includes: a third functional layer attached to the second functional layer, wherein the third functional layer is a silver layer; wherein the distance between the four edges of the composite electrode formed by the first functional layer, the second functional layer and the third functional layer and the four edges of the MOV substrate is 0.1-3mm.

[0007] The present invention further comprises that the thickness of the first functional layer is 50 nanometers to 20,000 nanometers, the thickness of the second functional layer is 50 nanometers to 20,000 nanometers, and the thickness of the third functional layer is 50 nanometers to 20,000 nanometers.

[0008] The present invention further comprises that the second functional layer is formed by vacuum sputtering.

[0009] This utility model further includes the following features:

[0010] The third functional layer is formed by vacuum sputtering.

[0011] In a further embodiment of this invention, the first functional layer is a chromium layer.

[0012] In a further embodiment of this invention, the first functional layer is a molybdenum layer.

[0013] In a further embodiment of this invention, the first functional layer is a titanium nitride layer.

[0014] The present invention further provides that, when the first functional layer is a chromium layer, its peel strength at the interface with the MOV substrate is ≥15N / cm.

[0015] The present invention further provides that, when the first functional layer is a titanium nitride layer, the sheet resistance change rate is ≤1.5% after heat treatment at 260°C for 1 hour.

[0016] The beneficial effects of this utility model are as follows: This utility model uses materials such as chromium, titanium nitride, or titanium layer as the first functional layer, which greatly improves the peel strength between the electrode and the MOV substrate and effectively solves the problem of electrode delamination. Attached Figure Description

[0017] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings:

[0018] Figure 1 This is a schematic diagram of the structure of Embodiment 1 of this utility model. Detailed Implementation

[0019] The following will describe in detail the implementation of this application with reference to the accompanying drawings and embodiments, so that the implementation process of how this application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0020] In existing technologies, varistors used in surge protectors typically employ silver as the electrode material. While silver possesses excellent conductivity, it is relatively soft, has a low melting point, and exhibits insufficient adhesion to the substrate. Under repeated lightning strikes or high-current surges, the silver electrodes are prone to detachment or poor contact due to low adhesion or electromigration, leading to decreased product performance or even failure. For instance, in high-temperature or high-current surge scenarios, physical defects in the silver electrodes may cause separation between the electrodes and the substrate, resulting in protection failure.

[0021] To address the aforementioned issues, an electrode structure that can both ensure conductivity and improve adhesion is needed. Analysis revealed that a single metal layer cannot simultaneously achieve both conductivity and interfacial bonding strength. If a multi-layer composite structure is used, the bottom layer material must possess high bonding strength, and the top layer material must possess high conductivity. Further consideration of the matching of material thermal expansion coefficients and process feasibility led to the final decision to combine a high-bonding-strength material layer with a highly conductive metal layer sequentially deposited on the substrate surface.

[0022] Therefore, this application proposes a varistor with a multilayer composite electrode structure, including an MOV substrate; a first functional layer directly attached to the surface of the MOV substrate, which is composed of one or more materials selected from titanium, nickel-chromium alloy, chromium, molybdenum, tantalum, titanium nitride, or nickel; a second functional layer attached to the first functional layer, which is a copper layer; the distance between the four edges of the composite electrode and the four edges of the MOV substrate can be 0.1-3 mm.

[0023] The MOV substrate refers to a varistor ceramic substrate primarily composed of zinc oxide and doped with metal oxides, which can be fabricated using a sintering process and serves as the core functional component of the varistor. The first functional layer is a transition layer directly deposited on the MOV substrate surface, typically formed using vacuum sputtering. It enhances the bonding strength between the electrode and the substrate; for example, a chromium layer improves interfacial adhesion, and a titanium nitride layer suppresses interfacial diffusion at high temperatures. The second functional layer is a conductive layer covering the first functional layer, typically formed by electroplating or sputtering to create a copper layer, providing a low-resistance current path. The composite electrode edge distance refers to the distance between the outer edge of the electrode and the edge of the substrate. For example, a masking process can be used to control the deposition area, preventing the electrode from extending to the substrate edge and causing a short circuit risk. Specifically, the first functional layer is formed on the MOV substrate surface through physical vapor deposition. This layer forms chemical bonds or mechanical interlocks with the substrate surface, thereby improving the interfacial bonding strength. Subsequently, a copper layer is deposited on the surface of the first functional layer as the second functional layer, utilizing the high conductivity of copper to reduce the overall electrode resistance. The four edges of the composite electrode are kept at a certain distance from the edge of the substrate, for example, by adjusting the mask size. This can prevent the electrode from peeling off at the edges under high temperature or mechanical stress, and at the same time avoid uneven electric field distribution at the edge of the substrate due to insufficient electrode coverage.

[0024] Compared to existing technologies, which use a single material layer for silver electrodes, this solution introduces a composite structure of a first functional layer and a second functional layer, significantly improving the bonding strength between the electrode and the substrate while maintaining conductivity. For example, chromium or titanium nitride as the first functional layer effectively suppresses interface peeling, while a copper layer as the second functional layer avoids deformation problems caused by the soft nature of the silver electrode. Furthermore, the spacing between the electrode edge and the substrate edge reduces the risk of electric field concentration in the edge region.

[0025] Through the above technical solution, this application solves the problem of detachment caused by insufficient adhesion of the silver electrode, and improves the stability of the electrode under multiple high-current impacts. The strong bonding force between the first functional layer and the substrate can suppress electrode peeling, the introduction of the copper layer enhances conductivity and anti-electromigration ability, and the electrode edge spacing design further reduces the risk of short circuit, thereby ensuring the reliable protection function of the varistor under complex working conditions.

[0026] This application further proposes a multilayer composite electrode structure varistor, including an MOV substrate, a first functional layer directly attached to the surface of the MOV substrate, a second functional layer attached to the first functional layer, and a third functional layer attached to the second functional layer. The third functional layer is a silver layer, and the distance between the four edges of the composite electrode formed by the first, second, and third functional layers and the four edges of the MOV substrate is 0.1-3 mm.

[0027] The third functional layer refers to the metal overlay layer located on the surface of the second functional layer. This can be achieved by depositing silver material using a vacuum sputtering process, providing a conductive interface and welding contact surface. The distance between the four edges of the composite electrode and the four edges of the MOV substrate refers to the coverage area of ​​each functional layer on the substrate surface. This can be achieved by controlling the sputtering mask size or using laser cutting technology, ensuring a buffer zone between the electrode edges and the substrate edges.

[0028] Specifically, the silver layer, as the outermost electrode, forms a stable connection with the external welding material, while the copper layer, as the intermediate layer, enhances the mechanical strength of the electrode structure. By limiting the distance between the edge of the composite electrode and the edge of the substrate, the problem of interface stress concentration caused by insufficient electrode coverage or excessive extension can be avoided. The functional layers are deposited layer by layer to form the overall structure, and the silver layer can maintain its conductivity stability even at high temperatures.

[0029] Compared to existing technologies, current MOV electrodes use only a single silver layer structure, which is prone to detachment due to insufficient adhesion. This solution, however, introduces a copper layer as an intermediate transition layer, effectively improving the bonding strength between the silver layer and the substrate. Simultaneously, the defined edge distance of the composite electrode avoids the problem of inaccurate electrode coverage in traditional processes, thereby reducing the risk of interface defects.

[0030] Through the above technical solution, this application can improve the structural stability of the silver electrode under multiple high current impacts, reduce poor contact caused by electromigration, and maintain the high conductivity of the electrode to ensure that the varistor maintains reliable protection performance during long-term use.

[0031] This application further proposes that the thickness of the first functional layer is 50 nanometers to 20,000 nanometers, the thickness of the second functional layer is 50 nanometers to 20,000 nanometers, and the thickness of the third functional layer is 50 nanometers to 20,000 nanometers.

[0032] The thickness of the first functional layer refers to the vertical dimension of the metal or alloy transition layer directly attached to the MOV substrate surface. This thickness can be achieved by controlling the deposition rate in stages using a vacuum sputtering process. This thickness range ensures uniform coverage of the transition layer on the substrate surface and maintains sufficient adhesion. The thickness of the second functional layer refers to the vertical dimension of the copper conductive layer. This thickness can be achieved by adjusting the sputtering time to control the total deposition amount. This thickness range ensures conductivity while avoiding interfacial stress caused by differences in thermal expansion coefficients due to excessive thickness. The thickness of the third functional layer refers to the vertical dimension of the silver solder layer. This thickness can be achieved by stacking multiple sputtering processes. This thickness range balances solderability and material cost.

[0033] Specifically, when constructing a composite electrode consisting of a chromium layer, a copper layer, and a silver layer sequentially on the surface of an MOV substrate, the thickness of each layer is controlled within the range of 50-20,000 nanometers. If the transition layer thickness is below the lower limit, it may not completely cover microscopic defects on the substrate surface; if it is above the upper limit, excessive internal stress may lead to interlayer delamination. Within this range, the copper layer thickness can form a continuous conductive network while avoiding a decrease in the overall flexibility of the electrode due to excessive thickness. The silver layer thickness, within this range, satisfies the metal quantity requirements of the welding process while preventing cost waste caused by excessive precious metal deposition.

[0034] Compared to existing technologies, traditional silver electrodes typically employ only a single material layer with coarse thickness control, resulting in insufficient adhesion between the electrode and the substrate and susceptibility to electromigration at high temperatures. This solution, by defining a precise thickness range for three functional materials, creates a gradient transition structure at the interface between each layer, effectively suppressing thermal stress concentration.

[0035] Through the above technical solution, this application can improve the structural stability of composite electrodes under lightning strikes and prevent conductive failure caused by interlayer delamination. Precisely controlled layer thickness ensures that the electrode maintains the synergistic effect of each functional layer when subjected to high current impacts, avoiding overall failure caused by defects in a single material.

[0036] This application further proposes the deposition of a second functional layer using a vacuum sputtering process. Vacuum sputtering refers to a physical vapor deposition method where high-energy particles bombard the surface of a target material in a vacuum environment, causing target atoms or molecules to detach and deposit onto the substrate surface to form a thin film. Specifically, magnetron sputtering, radio frequency sputtering, or DC sputtering equipment can be used. This process enables a copper layer to uniformly cover the surface of the first functional layer in a highly dense, low-porosity state, thereby enhancing the adhesion between the copper layer and the underlying material and suppressing electromigration. Specifically, in a multilayer composite electrode structure, when the copper layer is deposited as the second functional layer on the surface of the first functional layer, vacuum sputtering allows copper atoms to be deposited directionally in a high-kinetic-energy state under vacuum conditions, forming an impurity-free copper layer with a tightly packed lattice. This dense structure reduces internal defects in the copper layer, lowers the risk of material migration due to localized hot spots during current flow, and avoids the interfacial corrosion problems caused by solution residues in traditional electroplating processes.

[0037] Compared to existing technologies, traditional electrode fabrication processes typically involve forming the copper layer through electroplating or chemical deposition. These methods are prone to introducing bubbles, impurities, or porous structures within the copper layer, and are susceptible to interfacial delamination under high temperatures or high current impacts. In contrast, the copper layer formed by vacuum sputtering exhibits higher purity and density, significantly enhancing its bonding strength with the first functional layer, thereby effectively suppressing delamination failure of the electrode under lightning strikes. Through this technical solution, this application addresses the problem of insufficient electrode adhesion caused by structural defects in traditional copper layer fabrication processes. This allows the composite electrode to maintain stable conductivity and mechanical strength even under repeated high current impacts, preventing poor contact caused by copper layer detachment.

[0038] This application further proposes that the third functional layer is formed by vacuum sputtering.

[0039] Vacuum sputtering is a physical vapor deposition method that uses high-energy particles to bombard a target material in a vacuum environment, causing the target atoms to detach and deposit on the substrate surface to form a thin film. Specifically, it can be achieved using magnetron sputtering or DC sputtering equipment. This process can form a dense and uniform metal layer. The silver layer refers to a conductive layer composed of metallic silver with a purity higher than 99.9%, which can be achieved using a silver target as the sputtering source. This material possesses high conductivity and solderability.

[0040] Specifically, during vacuum sputtering deposition on the copper surface of the second functional layer, silver atoms are bombarded by high-energy argon ions within the vacuum chamber, detaching from the target and uniformly covering the copper surface with a linear trajectory. By controlling the sputtering power and substrate temperature during the deposition process, the silver atoms form an atomic-level bonding interface with the copper layer. The deposited silver layer exhibits a continuous, pore-free structure, thereby enhancing interlayer bonding while maintaining conductivity.

[0041] Compared to existing technologies, traditional silver electrodes often employ electroplating or coating processes, which easily generate grain boundary pores within the silver layer and result in weak adhesion to the substrate. In contrast, the silver layer formed by vacuum sputtering forms a metallic bond with the copper layer, with no oxide inclusions at the interface, significantly improving interlayer adhesion. At the same time, the dense structure effectively suppresses electromigration.

[0042] Through the above technical solution, this application solves the problem of silver electrode detachment due to insufficient adhesion and improves the structural stability of the electrode under lightning strikes. The continuous surface of the dense silver layer enhances the uniformity of conductivity, avoids welding failure caused by local overheating, and the non-porous structure formed by the sputtering process reduces the risk of silver layer oxidation, ensuring the long-term reliability of the electrode.

[0043] This application further proposes that the first functional layer is a chromium layer. The chromium layer refers to an intermediate layer composed of metallic chromium, which can be deposited using a vacuum sputtering process and directly attached to the surface of the MOV substrate. As a transition layer, the chromium layer enhances the interfacial adhesion with the MOV substrate and provides a stable foundation for the subsequent copper layer.

[0044] Specifically, a chromium layer is uniformly deposited on the surface of the MOV substrate using a vacuum sputtering process, forming a dense and continuous metal layer. This layer maintains structural stability under high temperature or high current impact, reduces interfacial stress caused by differences in thermal expansion coefficients, and thus suppresses the risk of electrode delamination. Furthermore, the chromium layer acts as a barrier layer, reducing the diffusion of copper atoms into the MOV substrate and preventing electromigration from affecting substrate performance.

[0045] Compared to existing technologies, where silver electrodes are directly attached to the MOV substrate, the weak interfacial bonding between silver and the substrate makes them prone to detachment under repeated impacts. This solution, however, introduces a chromium layer as an intermediate layer, significantly improving the interfacial bonding strength between the electrode and the substrate. Simultaneously, the high-temperature resistance of chromium enhances the electrode structure's resistance to thermal shock.

[0046] Through the above technical solution, this application solves the problem of detachment caused by low adhesion of silver electrodes, improves the stability of electrodes under lightning strikes or multi-pulse high current impacts, and extends the service life of varistor by suppressing electromigration.

[0047] This application further proposes a multilayer composite electrode structure varistor, including an MOV substrate; a first functional layer directly attached to the surface of the MOV substrate, the first functional layer being a molybdenum layer; and a second functional layer attached to the first functional layer, the second functional layer being a copper layer; wherein the distance between the four edges of the composite electrode formed by the first functional layer and the second functional layer and the four edges of the MOV substrate is 0.1-3 mm.

[0048] The molybdenum layer refers to an intermediate transition layer composed of metallic molybdenum, which can be formed using a vacuum sputtering process. The thickness can be controlled by adjusting the sputtering power and deposition time. The molybdenum layer forms a stable interface between the MOV substrate and the copper layer, suppressing electromigration.

[0049] Specifically, the molybdenum layer, as an intermediate functional layer, is directly applied to the surface of the MOV substrate. Its high melting point and chemical stability allow it to withstand thermal stress under repeated high-current impacts. The copper layer is indirectly attached to the MOV substrate through the molybdenum layer, avoiding interfacial reactions that might occur from direct contact between copper and the MOV substrate. The edges of the composite electrode are maintained at a certain distance from the edges of the substrate, for example, 0.1-3 mm, to prevent edge peeling of the electrode material during processing or use.

[0050] Compared to existing technologies, when silver is used as the electrode material, the bonding strength between the silver layer and the MOV substrate is relatively low, and electromigration easily occurs under high temperature or high current impact. The molybdenum layer, as an intermediate layer, not only improves the bonding force between the electrode and the substrate, but its high melting point also inhibits the softening or melting of the electrode material under high temperature conditions, preventing electrode detachment.

[0051] Through the above technical solution, this application solves the problems of low adhesion of silver electrodes and poor contact caused by electromigration. The molybdenum layer, as an intermediate transition layer, enhances the mechanical and thermal stability of the electrode structure and is suitable for varistor applications that need to withstand multiple large current impacts.

[0052] This application further proposes that the first functional layer is a titanium nitride layer. The titanium nitride layer refers to a ceramic material layer formed by the combination of nitrogen and titanium elements, specifically achieved by forming a dense titanium nitride thin film on the surface of an MOV substrate using physical vapor deposition. This material possesses a high melting point, high hardness, and excellent chemical stability, maintaining structural integrity even at high temperatures. The MOV substrate refers to a varistor ceramic matrix with zinc oxide as the main component and doped with metal oxides, specifically prepared into a disc-shaped structure with nonlinear current-voltage characteristics through a sintering process.

[0053] Specifically, a titanium nitride layer is directly deposited on the surface of the MOV substrate as the bottom functional layer of the electrode, utilizing the excellent interfacial bonding properties between titanium nitride and the ceramic substrate to form a stable contact. The titanium nitride layer does not soften or decompose during subsequent high-temperature welding, effectively preventing the diffusion and penetration of copper or silver layers into the ceramic substrate. By controlling the deposition process parameters, a uniform and dense microstructure can be formed in the titanium nitride layer, avoiding interlayer delamination caused by localized hot spots when subjected to high current surges.

[0054] Compared to existing technologies, when current electrodes employ a single silver layer structure, the difference in thermal expansion coefficients between the silver material and the ceramic substrate easily leads to interfacial stress concentration, resulting in cracks under temperature cycling. In contrast, the thermal expansion coefficient of the titanium nitride layer falls between that of the ceramic substrate and the copper layer, enabling the formation of a gradient transition structure and significantly reducing interfacial thermal stress. Furthermore, titanium nitride exhibits superior electrical conductivity compared to pure chromium or molybdenum, which helps reduce the overall electrode resistance.

[0055] Through the above technical solution, this application solves the problem of silver electrode detachment due to insufficient adhesion and improves the structural stability of the electrode under high-temperature environments. The titanium nitride layer, as a barrier layer, effectively suppresses the electromigration of metal atoms, ensuring that the electrode maintains reliable electrical connection even after multiple high-current impacts. This structural design also takes into account the conductivity and mechanical strength of the electrode, extending the service life of the varistor under harsh operating conditions.

[0056] This application further proposes that when the first functional layer is a chromium layer, its peel strength at the interface with the MOV substrate is ≥15 N / cm.

[0057] The chromium layer refers to an intermediate bonding layer composed of metallic chromium, which can be deposited on the surface of an MOV substrate using a vacuum sputtering process. This layer enhances the adhesion between the electrode and the substrate through chemical bonding and mechanical interlocking with the MOV substrate surface. Peel strength refers to the maximum tensile force per unit width of the interface layer in the vertical direction. This can be controlled by adjusting the sputtering process parameters to manage the chromium layer's crystallization state and the interface bonding quality, ensuring that the interface bonding strength meets predetermined targets.

[0058] Specifically, a chromium layer is placed as an interlayer between the MOV substrate and the copper layer. Its high reactivity allows chromium atoms to form stable chemical bonds with oxygen elements in the MOV substrate, while its dense crystal structure fills the micropores on the substrate surface, creating a mechanical anchoring effect. When the copper layer is heated or subjected to external forces, the chromium layer distributes the stress evenly throughout the substrate through strong interfacial bonding, preventing delamination failure at the electrode edges due to stress concentration.

[0059] In some specific embodiments, the chromium layer can be formed into a columnar crystal structure by adjusting the sputtering power and substrate temperature. The longitudinal arrangement of the columnar crystals is beneficial to enhancing the interfacial bonding strength. The substrate surface can be pre-cleaned with plasma to remove the oxide layer and improve the wettability of the chromium layer deposition.

[0060] Compared to existing technologies, when silver electrodes are directly deposited on MOV substrates, the interfacial bonding between silver and the zinc oxide substrate relies solely on physical adsorption. In contrast, the chromium layer forms a dual bonding mechanism through chemical bonding and mechanical interlocking. Silver electrodes are prone to interfacial separation under high temperatures or mechanical stress, while the composite electrode supported by the chromium layer can withstand higher levels of thermal shock and mechanical loads.

[0061] Through the above technical solution, this application effectively improves the bonding reliability between the electrode and the substrate. When subjected to multiple high current impacts or temperature changes, the composite electrode will not cause an increase in contact resistance due to interface peeling, thereby maintaining a stable overvoltage protection function.

[0062] This application further proposes that when the first functional layer is a titanium nitride layer, and after heat treatment at 260°C for 1 hour, the sheet resistance change rate is ≤1.5%.

[0063] The titanium nitride layer refers to a compound material layer composed of nitrogen and titanium elements. It can be formed on the surface of an MOV substrate using physical vapor deposition or chemical vapor deposition processes. This material possesses a high melting point, low resistivity, and excellent thermal stability, maintaining structural stability at high temperatures. Sheet resistance change rate refers to the relative change in resistivity per unit area before and after heat treatment. It can be measured using a four-probe method or a non-contact resistance meter. This indicator reflects the material's electrical conductivity stability under high-temperature conditions.

[0064] Specifically, when the titanium nitride layer is used as the first functional layer, its crystal structure is less prone to phase transitions or oxidation at high temperatures, thus suppressing interfacial stress caused by differences in thermal expansion coefficients. During heat treatment at 260℃, a stable interfacial bond is formed between the titanium nitride layer and the MOV substrate, while its own resistivity is less affected by temperature. By controlling the density and thickness uniformity of the titanium nitride layer, the fluctuation of carrier mobility during heat treatment can be further reduced, thus limiting the rate of change of sheet resistance to a low level.

[0065] The specification and claims use certain terms to refer to specific components. Those skilled in the art will understand that hardware manufacturers may use different names to refer to the same component. This specification and claims do not distinguish components based on differences in name, but rather on differences in function. The term "comprising" throughout the specification and claims is an open-ended term and should be interpreted as "comprising but not limited to." "Approximately" means that within an acceptable margin of error, those skilled in the art can solve the technical problem and substantially achieve the technical effect within a certain margin of error.

[0066] The foregoing description illustrates and describes several preferred embodiments of the present invention. However, as previously stated, it should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the inventive concept described herein through the foregoing teachings or techniques or knowledge in related fields. Any modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.

Claims

1. A varistor with a multilayer composite electrode structure, characterized in that, include: MOV substrate; A first functional layer is directly attached to the surface of the MOV substrate. The first functional layer is a layer selected from titanium, nickel-chromium alloy, chromium, molybdenum, tantalum, titanium nitride, or nickel. A second functional layer is attached to the first functional layer. The second functional layer is a copper layer. The distance between the four edges of the composite electrode formed by the first functional layer and the second functional layer and the four edges of the MOV substrate is 0.1-3 mm.

2. The varistor with a multilayer composite electrode structure according to claim 1, characterized in that, Also includes: A third functional layer is attached to the second functional layer, wherein the third functional layer is a silver layer; The distance between the four edges of the composite electrode formed by the first functional layer, the second functional layer and the third functional layer and the four edges of the MOV substrate is 0.1-3 mm.

3. The varistor with a multilayer composite electrode structure according to claim 2, characterized in that: The thickness of the first functional layer is 50 nanometers to 20,000 nanometers. The thickness of the second functional layer is 50 nanometers to 20,000 nanometers. The thickness of the third functional layer is 50 nanometers to 20,000 nanometers.

4. A varistor with a multilayer composite electrode structure according to claim 1 or 2, characterized in that: The second functional layer is formed by vacuum sputtering.

5. A varistor with a multilayer composite electrode structure according to claim 2, characterized in that: The third functional layer is formed by vacuum sputtering.

6. A varistor with a multilayer composite electrode structure according to claim 1, characterized in that: The first functional layer is a chromium layer.

7. A varistor with a multilayer composite electrode structure according to claim 1, characterized in that: The first functional layer is a molybdenum layer.